Forage and seed production of Panicum virgatum, Tripsacum dactyloides and Sporobolus airoides in Tulancingo, Hidalgo: Forraje y semilla de pastos nativos - Rodríguez-Ortega, Leodan Tadeo; Verde-Villegas, Daniel Alejandro; Hernández-Guzmán, Filogonio Jesús; Castrellón-Montelongo, Jorge Luis; Rodríguez-Ortega, Alejandro (Ecosistemas y Recursos Agropecuarios, 2021)
Given the need to transfer less-used grass technology in irrigation water and continue with livestock activity in the Tulancingo Valley, the objective of the study was to evaluate three mexican grasses Panicum virgatum, Sporobolus airoides and Tripsacum dactyloides in forage production, stem population density, production of seed and characterization of seeds in a physical and physiological way. The study was carried out from april to august and from august to december 2020 under drip irrigation conditions with 10 transplants in 12 m2 from adult plants. The highest yield of forage (sum of two cycles) and leaves are operated on P. virgatum (3.59 t DM ha-1; P < 0.0001), followed by T. dactyloides (1.15 t DM ha-1) and S. airoides (0.719 t DM ha-1). The accumulated live stem population in T. dactyloides was 216, in P. virgatum 187 and in S. airoides 82 stems per plant-1 (P < 0.0001). The production of diaspores in sum of the two cycles, in P. virgatum was 147 kg ha-1, similar (P > 0.05) to T. dactyloides, however, the cupules with incipient physical purity (0.79%). The highest physical purity (14.08 kg ha-1; P < 0.0001) and viable pure seed (12.3 kg ha-1; P < 0.0001) was observed in Sporobolus airoides.